2006
DOI: 10.1128/jvi.80.7.3617-3623.2006
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Cost of Escape Mutations in p24 Gag in Association with Control of Human Immunodeficiency Virus Type 1

Abstract: Mutational escape by human immunodeficiency virus (HIV) from cytotoxic T-lymphocyte (CTL) recognitionis a major challenge for vaccine design. However, recent studies suggest that CTL escape may carry a sufficient cost to viral replicative capacity to facilitate subsequent immune control of a now attenuated virus. In order to examine how limitations can be imposed on viral escape, the epitope TSTLQEQIGW (TW10 [Gag residues 240 to 249]), presented by two HLA alleles associated with effective control of HIV, HLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

47
468
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 411 publications
(521 citation statements)
references
References 36 publications
47
468
5
Order By: Relevance
“…In particular, the extreme conservation and intolerance of escape variations in Gag p24 indicate that it may be a critical target for vaccine design (35,36). There is only one well-defined HLA-A2-restricted epitope in p24, abbreviated as TV9 (TLNAWVKVV, Gag p24 19 -27 ).…”
mentioning
confidence: 99%
“…In particular, the extreme conservation and intolerance of escape variations in Gag p24 indicate that it may be a critical target for vaccine design (35,36). There is only one well-defined HLA-A2-restricted epitope in p24, abbreviated as TV9 (TLNAWVKVV, Gag p24 19 -27 ).…”
mentioning
confidence: 99%
“…The hypothesis that CTL escape mutants have reduced fitness is supported by studies of simian immunodeficiency virus in which cloned CTL escape mutants obtained from a macaque showed slowed growth in cell culture and reversion to the CTL-susceptible wild-type sequence after inoculation into macaques lacking the major histocompatibility class I determinants necessary for the recognition of the mutant epitopes (62). Studies of escape mutants in the Gag p24 protein demonstrated that these mutations do confer substantial reductions in replication fitness, as measured in a multiplecycle cell culture assay (117,134). It is interesting that these escape mutants, when they occur, are seen primarily in patients with HLA types that are associated with the successful control of HIV viremia.…”
Section: Outcomes In Primary Hiv-1 Infectionmentioning
confidence: 76%
“…Some examples of measuring virus directly include quantitation of a viral protein, such as p24, by enzyme-linked immunosorbent assay (106,156,163); measurement of reverse transcriptase activity (164, 175); and quantitation of proviral DNA (116). In addition, in growth competition assays, the relative amounts of test and reference strains can be quantified by sequence analysis of proviral DNA or viral RNA (65,69,78,86,117,154,155,169,174), heteroduplex tracking assays (HTAs) (140), or allele-specific real-time PCR (33,142,176). It should be noted that the latter methods do not provide information on the extent of viral replication.…”
Section: Cell Culture Assaysmentioning
confidence: 99%
See 2 more Smart Citations